The Malaysian experience on covid-19 pandemic: the articles review and potential research opportunities from the organizational and accounting perspectives - Sulaiman Tahajuddin (International Journal of Advances in Engineering and Management, 2021)
The main aim of this paper is to present the reviews of the recent literature related to the impacts of Covid-19 on the Malaysian business activities in some industries especially the tourism in specific, and wider business activities in general. Undoubtedly, Covid-19 has badly impacted the social, economic and political aspects of many nations which has eventually impacted many lives as well. In Malaysia, it is evident that Covid-19 has mainly caused business activities especially in tourism industry badly affected despite the relentless government’s mitigation plans and actions. Based on the reviews of recent related literature, it is found that the majority of the published papers only focused on the macro and national level business activities impacts and therefore not much is known at the micro societal and organizational levels. Within the context of Malaysia, this paper suggests that more research and papers to be conducted and more focused on the societal and organizational levels either employing quantitative and/or qualitative methods. To further make it more visible, the impacts of Covid-19 could be better understood through the inclusion of accounting perspective in the future research on this pandemic and its impact on the societal and organizational levels.